2017
DOI: 10.4018/ijdet.2017100106
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Online Discussions on Web Based Assessments

Abstract: The practice of including online discussion posts to traditional courses is increasing. Online discussions allow for active learning to occur as students express their ideas and respond to others. The time and thought provided by online discussion posts allows students to utilize higher level cognitive skills. Web-based assessments are another technology tool that instructors are including in their courses. This study examined the impact of online discussion posts on achievement of web-based assessments for an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…However, it was also found that students were not using any discussion group (Irum, 2018;Powell, et. al, (2017) found that discussion group provides opportunities for students and teachers to share notes solve difficult topics, teachers post quiz or test for students to solve.…”
Section: Discussionmentioning
confidence: 99%
“…However, it was also found that students were not using any discussion group (Irum, 2018;Powell, et. al, (2017) found that discussion group provides opportunities for students and teachers to share notes solve difficult topics, teachers post quiz or test for students to solve.…”
Section: Discussionmentioning
confidence: 99%